Major farm practice report in JM (Jabelosa-Marcon) and Saint Jude Brooding Farm - Gaditano, Felicisima A.; Peñeda, Genna; Lagman, Ner B. (Tacloban City Agricultural and Rural Development, University of the Philippines College Tacloban, 1981)
This study describes the observed operations management of JM (Jabelosa-Marcon) and Saint Jude Brooding Farm in Cebu.
Undergraduate thesis (Bachelor of Science in Animal Science)--University of the Philippines College Tacloban, Summer 1981.
Keywords: JM (Jabelosa-Marcon); Saint Jude Brooding Farm; Poultry -- Farm management and production; Poultry industry -- Cebu; Poultry breeding